Kedudukan dan Fungsi Hadis: Analisis Rasional, Teologis Serta Fungsinya Dalam Hukum Islam - Ahmad Sayuti; M. Indra Kurniawan; Aco Karso; Didin (Jurnal Pendidikan Agama Islam, 2026)
The Hadith's status as the second primary source of Islamic law continues to face intellectual scrutiny, with debates focusing on its authenticity and contemporary relevance. Prevailing scholarship often treats the rational (‘aqli) and theological (naqli) bases of Hadith authority separately from its practical legal applications, resulting in a fragmented understanding. This study bridges that divide by conducting an integrated analysis of Hadith’s foundational principles and its operational functions within Islamic legal theory. A qualitative, library-based methodology is employed, utilizing primary sources (the Qur’an and Hadith) and secondary academic literature, with data analyzed thematically following the Miles and Huberman framework. Results demonstrate that Hadith’s authority is firmly supported by rational foundations, serving as an indispensable explanatory (bayan) mechanism for the Qur’an, reinforced by prophetic faith, scholarly consensus (ijma‘), the doctrine of prophetic infallibility (‘ismah), and the Prophet’s exemplary conduct (uswah hasanah). Theologically, its position is definitive (qath‘i), derived from explicit Qur’anic mandates for obedience to the Messenger and Prophetic declarations that establish the Sunnah’s complementary authority. The study further identifies six core legal functions through which Hadith operates: affirmation (taqrir), elaboration (tafsīl), restriction (taqyīd), specification (takhsīs), independent legislation (tasyrī‘), and abrogation (naskh). This research concludes that Hadith transcends a purely formal legal source, functioning instead as a dynamic hermeneutical instrument that sustains the relevance, justice, and adaptability of Islamic law across time.